Inhibition of Streptococcus mutans by a commercial yogurt drink - Ching-Yi Wu; Ssu-Jung He; Kwei Mar; Chin-Ying Stephen Hsu; Shan-Ling Hung (Elsevier, 2019)
Background/Purpose: Studies have been focused on using probiotics to prevent caries. The lactobacillus probiotic bacteria in Yakult® (LcY) has been shown to inhibit the growth or biofilm formation of Streptococcus mutans. However, sucrose in Yakult® raised concerns. The purpose of this study was to determine effects of Yakult® on the growth and adhesion of S. mutans. Materials and methods: S. mutans was grown in serial diluted Yakult®, filtered Yakult® or 20% heated Yakult®. S. mutans was co-cultured with LcY in media with or without diluted filtered Yakult®, or in LcY grown in media with or without sugars. Colony forming units and pH values of bacterial cultures were determined. SYTO 9-stained adhered bacteria were observed. Results: Yakult® inhibited the growth of S. mutans. Filtering or heating Yakult® reduced its inhibitory ability against S. mutans. The inhibitory effect of LcY against S. mutans was enhanced when cultured in the presence of 20% filtered Yakult®. LcY cultured in sucrose media for 24 h inhibited the growth of S. mutans, but this effect was less evident when LcY was grown for 48 h. LcY grown in glucose or lactose media similarly reduced S. mutans growth. Culturing S. mutans with LcY grown in sucrose or glucose media reduced bacterial adhesion. However, co-culturing S. mutans with LcY grown in the lactose media did not decrease bacterial adhesion. Conclusion: Yakult® and its probiotic content may inhibit S. mutans growth and the effect may be moderated by the type of sugar added for LcY cultivation. Keywords: Streptococcus mutans, Lactobacillus casei strain Shirota, Yogurt drink